Enhancing English Language Learning through Deep Learning Approaches in MTS Al-Amin Kampung Pajak - Dewi Nurmala; Ratna Dewanti (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to explore the potential of integrating deep learning approaches into English language learning at MTS Al-Amin Kampung Pajak. The approach is expected to enhance the effectiveness of English instruction by providing more personalized, interactive, and adaptive learning tools. This research uses a qualitative descriptive method with a case study design, involving interviews with English teachers, classroom observations, and document analysis. The findings indicate that while both teachers and students have a positive attitude toward the use of technology, the main challenges lie in limited technological infrastructure and the teachers’ preparedness to integrate technology into their teaching. Deep learning tools such as AI-powered writing assistants, pronunciation trainers, and adaptive learning apps can be effectively integrated to enrich the students' learning experiences. This study recommends investing in technological infrastructure, providing professional development for teachers, and implementing a phased approach to introducing deep learning tools in the classroom.